2019
DOI: 10.21705/mcbs.v3i2.58
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of Osteoblast Cell Proliferation and Osteocalcin Expression in Cuttlefish Bone and Bovine Bone Xenograft

Abstract: Background: Cuttlefish bone Xenograft, calcium phosphate (CaP)-based biomaterial graft, offers an alternative and has been accepted for osteoconductive and probable osteo-inductive attributes. This study aims to compare the bone healing potential between the bovine-derived (BHA) and cuttlefish bone-derived (CHA).Materials and Methods: The study compared osteoblast cell proliferation of 27 New Zealand rabbits in 2.5 mm bone defect made in the femoral bone. The samples were divided into three groups, which were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…19 Other studies found that the cuttlefish bonegraft has the potency to induce osteoblast differentiation and proliferation. 7,20,21 This circumstance is postulated because of the presence of Mg²⁺ on the material, which was proven to promote osteogenesis. 22,23 Thus, cuttlefish bone powder poses low toxicity and ability to promote osteogenesis, prompting its possible application as bone graft material.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…19 Other studies found that the cuttlefish bonegraft has the potency to induce osteoblast differentiation and proliferation. 7,20,21 This circumstance is postulated because of the presence of Mg²⁺ on the material, which was proven to promote osteogenesis. 22,23 Thus, cuttlefish bone powder poses low toxicity and ability to promote osteogenesis, prompting its possible application as bone graft material.…”
Section: Discussionmentioning
confidence: 99%
“…The acute systemic toxicity examination in this study for PerOssal®, cuttlefish bone, and control groups showed minor acute systemic toxicity reaction and pyrogenicity, which is consistent with the previous experiment with rat fracture model. 6,7,19 Dogan and Okumus 8 reported that cuttlefish bone xenograft did not affect the physiological measurement of the NZ rabbit after 24 weeks of implantation, allowing the cuttlefish bone to become bone xenograft potential material. They also showed no increase in inflammatory cells histologically; thus, the graft does not cause inflammatory reactions.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Levels of osteocalcin and osteoblast cells are components used as markers of the bone healing process. 8 , 9 Sari et al . 10 studied the use of seashells and sea cucumber on the femoral defects of Wistar rats and found significant differences in the number of osteoblasts and osteoclasts between groups.…”
Section: Introductionmentioning
confidence: 99%